PERANG SALIB SERTA DAMPAKNYA BAGI DUNIA ISLAM DAN EROPA - Aniroh Aniroh (STAI Sufyan Tsauri Majenang, 2021)
Crusades were a series of waves of armed religious strife started by Christians in the period 1095-1291, with the aim of reclaiming Jerusalem and the